Interplay between structure and density anomaly for an isotropic core-softened ramp-like potential. - Oliveira, Alan Barros de (2012)
Using molecular dynamics simulations and integral equations wee investigate the structure, the thermodynamics, and the dynamics of a system of particles interacting through a continuous core-softened ramp-like interparticle potential. We found density, dynamic and structural anomalies similar to that found in water. Analysis of the radial distribution function for several temperatures at fixed densities shows a pattern that may be related to the origin of density anomaly.